(untitled) (World Economics and Finance Bulletin, 2022)
The manipulation of accounts and financial statements to hide the actual performance of companies in order to reach useful results for the company or some of its employees is what it means by creative accounting or profit management. Such methods are described as provided that it is practiced without exceeding the accepted accounting standards and principles but by exploiting the elements of flexibility and choice in those standards and principles . The practice of these methods has a very important effect in undermining market confidence in the information contained in the financial statements published by the companies